“Give Me Happiness” or “Take Away My Pain”: Explaining consumer responses to prescription drug advertising - Nithima Sumpradit; Richard P. Bagozzi; Frank J. Ascione; Len Tiu Wright (Cogent Business & Management, 2015)
We examine how consumers react to direct-to-consumer advertising (DTCA) by investigating the role of goal compatibility between motivation to process advertisements and consumer self-concept. Specifically, we examine the interaction between self-regulatory (prevention versus promotion) focus and self-construal orientation (independent versus interdependent) and find that prevention (versus promotion) focused consumers form stronger intentions to speak with physicians and are more likely to discuss an advertised drug, when the ad uses an interdependence self-construal theme, whereas promotion (versus prevention) focused consumers form stronger intentions to speak with physicians and are more likely to discuss an advertised drug, when the ad uses an independent self-construal theme. The above two-way interaction was further found to be governed by attitudes toward DTCA. Under goal compatibility, consumers who had positive or neutral attitudes toward DTCA (versus negative) had stronger (a) intentions to speak with physicians about the advertised drug, (b) stronger intentions to speak with physicians about high cholesterol, (c) greater likelihood of discussing the drug with health professionals, and (d) greater likelihood of requesting a prescription, yet did not differ in perceptions of drug benefits and risks. Hypotheses were tested on a sample of 197 female staff and retirees (aged 40–80 years) at a large university.
Keywords: 650